Phase II Trial of Capecitabine and Weekly Docetaxel for Metastatic Castrate Resistant Prostate Cancer - Vaishampayan, Ulka N. (2009)
PURPOSE: Synergy is observed with the combination of capecitabine and docetaxel due to docetaxel mediated up-regulation of thymidine phosphorylase. A phase II trial was performed with the combination for metastatic, castrate resistant prostate cancer. MATERIALS AND METHODS: Eligible patients had metastatic, castrate resistant prostate cancer, no prior chemotherapy for metastatic disease and normal organ function. Docetaxel (36 mg/m(2) per week intravenously) on days 1, 8 and 15, and capecitabine (1,250 mg/m(2) per day in 2 divided doses) on days 5 to 18 were administered in 28-day cycles. The response was assessed every 2 cycles. Biomarker correlative studies were performed on blood dihydropyrimidine dehydrogenase, and the thymidine phosphorylase-to-dihydropyrimidine dehydrogenase and thymidine synthase-to-dihydropyrimidine dehydrogenase ratios in available prostate tumor tissue. RESULTS: A total of 30 patients with a median age of 69 years were enrolled in the study. We noted bone pain in 21 patients (70%), Gleason score 8 or higher in 18 (60%), measurable disease progression in 9, bone scan progression in 18 and prostate specific antigen progression in 22. Grade 3 or 4 neutropenia was seen in 3 patients and grade 3 hand-foot syndrome was found in 2. No treatment related deaths occurred. A prostate specific antigen response of 50% or greater decrease was observed in 22 patients (73%), of whom 9 (30%) had 90% or greater decrease. A partial response was noted in 5 of 9 patients (56%) with measurable disease. Median time to progression was 6.7 months (90% CI 4.2–7.7) and median overall survival was 22.0 months (90% CI 18.4–25.3). CONCLUSIONS: The combination was well tolerated and it demonstrated favorable response rates with durable remission and survival outcomes.